Gastric bezoars in adults (2 cases) - Colet, Andrés; Segura, Daisy; Rodríguez, Gustavo; Cilleruelo, Roberto; Bruno, Gerardo; Estefan, Alberto; Praderi, Raúl (Cirugía del Uruguay, 1996)
The authors present two infrequent cases of gastric bezoar in the adult, one of which was a/so complicated with acute abdomen. The diagnosis was intraoperative in both cases. Different techniques were combined in order to so/ve their various associated intra-abdominal pathologies in only one surgery. The authors comment on non-surgica/ a!ternative therapies for non-complicated gastric bezoar without associated pathology.